Reframing Bioterrorism After The 2001 Anthrax Attack: Strategic Shifts In U.S. Counterterrorism Policy: Mengubah Perspektif Terorisme Biologis Pasca Serangan Antraks 2001: Pergeseran Strategis dalam Kebijakan Kontraterorisme AS - Callysta Emily Asterina; Imam Fadhil Nugraha (Indonesian Journal of Counter Terrorism and National Security, 2024)
This article examines the 2001 Anthrax attacks as a turning point in US counterterrorism strategy, emphasizing how the event redefined biological threats as matters of national security. Using information from intelligence reports, how governments have responded to this, and a theoretical framework based on Michel Foucault's idea of biopolitics, this study looks at intelligence failures and the move from reacting to counterterrorism to being proactive. The securitization of health is explored as a means by which microbial threats can be transformed into strategic tools for state control, with consequences for civil liberties, global diplomacy, and public trust. The article argues that bioterrorism, particularly the anthrax case, should be understood not only as a security breach, but also as a political event that altered the way in which the state governs life. By doing so, the study contributes to a deeper understanding of how non-traditional threats can reshape security frameworks in the modern era concerning to the topic discussed.